The Impact of Laughter Yoga on Mental Well-being of Cancer Patients under Chemotherapy - Mohammad Namazi Nia (Journal of Evidence-Based Care, 2019)
Background: It is generally accepted thatcancer affects the concept of mental well-being by changing the physical, psychological, spiritual, and social dimensions of the patient's life. Laughter yoga as one of the complementary therapies may promote mental well-being in patients undergoing chemotherapy. Aim: This study aimed to determine the effect of laughter yoga on the mental well-being of cancer patients undergoing chemotherapy. Method: This randomized controlled trial was conducted on 69 cancer patients undergoing chemotherapy at Reza Medical Center, Mashhad, Iran, in 2018. The intervention group was subjected to four 20-30 min sessions of laughter yoga prior to chemotherapy. On the other hand, the control group received routine self-care training. The mental well-being scores were measured using the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) before and after the laughter yoga sessions. Data were analyzed in SPSS software (version 20) using an independent t-test, Mann-Whitney test, Wilcoxon test, and repeated measures ANOVA. Results: According to the results,the mean age values of the patients were 49.0±9.6 and 45.2±12.6 years in the intervention and control groups, respectively. Regarding the independent t-test results, the mean post-test WEMWBS score in the intervention group (50.0±8.9) was significantly higher than that in the control group (47.9±10.4, P=0.004). Moreover, the repeated measures ANOVA showed a significant increase in the mean post-test WEMWBS score in the intervention group (P<0.001). Implications for Practice: Laughter yoga can promote the mental well-being of patients undergoing chemotherapy; therefore, its clinical applications are recommended in this study.